Extremal Values of the General Harmonic Index and General Sum-Connectivity Index of f-Benzenoids. (28th May 2022) - Ye, Qingfang; Li, Fengwei; Ye, Ruixuan
Abstract: The general harmonic index and general sum-connectivity index are two degree-based topological indices which reflect certain structural features of organic molecules. A fluoranthene-type benzenoid system ( f -benzenoid) is a polycyclic conjugated system obtained by joining two ordinary benzenoid hydrocarbons so as to form a five-membered ring. In this paper, by virtue of molecular structural analysis, we give the expressions for computing the general harmonic index and general sum-connectivity index of f -benzenoids, and we determine the extremal values of general harmonic index H α and general sum-connectivity index S α in f -benzenoids with h hexagons for some real number α. Especially, we give the extremal values of H α and S α in cata-catacondensed f -benzenoids with h hexagons.